Use of therapeutic milieu interventions in a psychiatric setting: A systematic review - C Xavier Belsiyal; Sreevani Rentala; Anindya Das (Wolters Kluwer Medknow Publications, 2022)
BACKGROUND: The therapeutic environment is commonly acknowledged as a significant influence on mental inpatient treatment experiences and outcomes. Therapeutic milieu interventions provide a distinct, secure hospital ward/unit atmosphere where patients with mental illness receive therapeutic interactions and collaborative attentiveness. The review aimed to explore the studies related to the role of a nurse using therapeutic milieu/milieu therapy in a psychiatric setting. MATERIALS AND METHODS: A systematic literature search was conducted between 1976 and 2021 using PsycINFO, Medline, Embase, and Scopus. A total of 13 papers were identified for a full review. RESULTS: A total of 70 studies were found, out of which 13 of them were analyzed. These studies looked at several therapeutic milieu concepts, such as therapeutic communication, patient satisfaction, nurse involvement, ward design and structure, and a mixture of therapeutic milieu concepts. Most of the studies explored the concepts of milieu therapy in community settings. CONCLUSION: In the mental health nursing literature, the milieu, as well as milieu therapy, is a well-debated subject. Though the importance of therapeutic milieu in psychiatric settings is recognized, empirical studies on milieu implementation are scarce. Therefore, research is needed to explore the effectiveness of milieu therapy in inpatient psychiatric care, which facilitates patient recovery, safety, and good interpersonal relationships.